OPTIMALISASI PEMBELAJARAN AL-QUR’AN MELALUI METODE UMMI DI DESA SIRNAJATI - Oktavia, Tiana; Ghofur, Abdul; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2025)
In line with the principles of tajwid science, the Ummi method is a technique for teaching reading the Koran that directly applies tartil reading. In actual use, the volume of this method varies depending on the child's age. Ummi's method begins with the study of the Koran and requires six volumes for teenagers and only three volumes for adults. Explaining how the Ummi technique is applied in learning the Qur'an and assessing its impact on the ability to read the Qur'an are the two main objectives of this approach. Research findings show that Ummi's approach to learning the Al-Qur'an is carried out methodically and in accordance with the basic competencies and indicators that have been identified. The Classical Reading and Listening Approach, which provides benefits in presenting content, is the delivery method used. Improvements in children's cognitive, affective and psychomotor skills show these benefits. Apart from that, Ummi's approach also has a huge impact in improving a person's ability to read the Al-Quran. The approach used in the learning process has a significant influence on the success or failure of education. Children who follow the correct approach can read the Koran according to the norms of tajwid (tartil), feel happy and enthusiastic about learning, read clearly, differentiate between short and long readings, and understand the word of Allah. lafadz (tafkhim and tarqiq), correct your own mistakes, and memorize juz 30 to juz 19 or even more than two juz.